P.(Asp47Asn) and p.(Thr62Met): non deleterious LDL receptor missense variants functionally characterized in vitro. Issue 1 (December 2018) - Benito-Vicente, A.; Siddiqi, H.; Uribe, K.; Jebari, S.; Galicia-Garcia, U.; Larrea-Sebal, A.; Stef, M.; Ostolaza, H.; Palacios, L.; Martin, C.
Abstract Familial Hypercholesterolemia (FH) is a common genetic disorder caused most often by mutations in the Low Density Lipoprotein Receptor gene (LDLr ) leading to high blood cholesterol levels, and ultimately to development of premature coronary heart disease. Genetic analysis and subsequent cascade screening in relatives allow diagnosis of FH at early stage, especially relevant to diagnose children. So far, more than 2300 LDLr variants have been described but only a minority of them have been functionally analysed to evaluate their pathogenicity in FH. Thus, identifying pathogenic mutations in LDLr is a long-standing challenge in the field. In this study, we investigatedin vitro the activity p.(Asp47Asn) and p.(Thr62Met)LDLr variants, both in the LR1 region. We used CHO-ldlA7 transfected cells with plasmids carrying p.(Asp47Asn) or p.(Thr62Met)LDLr variants to analyse LDLr expression by FACS and immunoblotting, LDL binding and uptake was determined by FACS and analysis of mutation effects was assessedin silico . Thein vitro activity assessment of p.(Asp47Asn) and p.(Thr62Met)LDLr variants shows a fully functional LDL binding and uptake activities. Therefore indicating that the three of them are non-pathogenic LDLr variants. These findings also emphasize the importance ofin vitro functional LDLr activity studies to optimize the genetic diagnosis of FH avoiding the report of non-pathogenic variants and possible misdiagnose in relatives if cascade screening is carried out.